Biodiversity study of several peatland types in Papua. Issue 1 (September 2020) - Sundari, S; Ibo, L K; Rahajoe, J S; Alhamd, L; Gunawan, H; Priyono, N C
Abstract: Research on biodiversity study of several peatland types in Papua had been carried out in Merauke and Mappi. The plot method was used for ecological research and interviews method for ethnobotany research. The results showed that the most important species which have the highest Importance Value Index (IVI) were Beilschmiedia sp., Carallia brachiate (Lour.) Merr., and Kibara coriacea (Blume) Hook. f. & A. Thomps. in Kaliki Village, whereas it was Melaleuca leucadendra (L.) L only in Marga Mulia Village, Merauke. The most important species which have the highest IVI were Semecarpus forstenii Blume, Archidendron clypearia (Jack) I.C. Nielsen, and Campnosperma auriculatum (Blume) Hook.f. in Khanami Village, while they were Calophyllum euryphyllum Lauterb, Diospyros toposiodes King & Gamble, and Syzygium effusum (A.Gray) Müll. Stuttg in Yame Village, Mappi. The plants are used for building materials and ships, medicinal materials, food ingredients, animal feed, energy-producing materials/firewood, and material in traditional rituals.